Analisis Nilai Ekonomi Museum T.B Silalahi Center Di Kecamatan Balige, Kabupaten Toba Samosir Dengan Menggunakan Pendekatan Metode Biaya Perjalanan - Daniel Holden; Nursiah Chalid; Nobel Aqualdo (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This research was carried out on the object Tourism of TB Silalahi Museum Centre in Toba Samosir regency of North Sumatra to determine the economic value of the environment and to look the influence of travel costs, income, and residence distance of respondents with the number of visitor who come to the TB Silalahi museum center. This research took a sample of 100 respondents of TB Silalahi Museum Center visitor. Data analysis methods that I used in this research were descriptive and quantitative methods. Quantitative analysis was performed by using multiple linear regression equation to the data collected in the form of numbers in tabulated form then discussed it with descriptive methods. In calculations, the economic value of TB Silalahi museum Center that based of approach travel cost is Rp 2,735,078,350. From the analysis, the rate coefficients of the variables that affect the number of visitor to the museum TB Silalahi Center are travel costs (X1) 0.0000142, income (X2) 0.00005032, and distance of residence of respondents to the tourist attractions (X3) -0.122. The results of testing research can also be known simultaneously (synchronously) showed significant effect in which the travel expenses, income and distance of the respondents. Travel expenses, income and distance respondents have significantly influence the number of museum TB Silalahi Center visitor. It is shown from the test results calculated that F (58,992)> F table (2.70). The partial test results showed only the income variable does not have significantly influence to the number of individual visitor who come to the TB Silalahi Museum Center.Keywords: TB Silalahi Museum Centre, Travel Cost Methode and Economic Value